Pelatihan Produk Bioteknologi untuk Praktikum Biologi Bagi Guru SMP di Kabupaten Tanggamus Propinsi Lampung - Kusuma Handayani; Christina Ekowati; Sumardi, M. Kanedi (Komunitas Dosen Indonesia, 2022)
Improvements in the quality of education from year to year are always strived for, both at the elementary, secondary, and tertiary levels. Efforts to improve the quality of education are influenced by the curriculum, textbooks, learning media, learning methods, and evaluation systems. The teacher as one of the spearheads in the community learning process does not escape the problem which is a problem for all levels of society. In the field, there are still many junior high school science teachers who have an inadequate background in Biology, especially in the field of Biotechnology. From the results of the initial survey, it can be seen that the condition of junior high school (SMP) teachers, especially in the field of science studies in Tanggamus Regency, that knowledge about the manufacture of fermented products is very minimal. Therefore, training is needed, so that junior high school science teachers can enrich Biology teaching materials related to biotechnology. This training activity is expected to be useful in helping science teachers in enriching learning materials in the field of biology in junior high schools and provide input for related institutions in improving the quality of teachers to become professionals. This service activity is carried out with several activities, namely lectures and direct practice of making biotechnology products such as kefir, yogurt, and tempeh. Evaluation of these activities will be carried out at the beginning of the training, during the training process, and at the end of the training. more than 50% of there were 3 participants at the time of the posttest